Inovasi Kuliner Lokal Dalam Rangka Meningkatkan Kunjungan Wisatawan Di Desa Pardinggaran, Kabupaten Toba - Muhammad Rizal Sitepu (Politeknik Pariwisata Medan, 2023)
Ombus-ombus typical Batak food is food that comes from the Batak language which means blowing. This food is called ombus-ombus because this food is usually eaten or served hot and that means that to enjoy this ombus you need to blow it first. Usually this food will be more delicious when served with sweet tea or hot coffee. It is not clear since when this confectionary began to